THE EFFECT OF COMPETENCE, COMPENSATION OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND PERFORMANCE OF EMPLOYEES IN LIFE INSURANCE COMPANIES IN BATAM CITY - Suhardi, Suhardi (Archives of Business Research, 2018)
This study aims to determine the effect of competence, compensation for organizational citizenship behavior (OCB) and job performance in life insurance companies in Batam City. The sample of this study was 244 respondents with the proportionate sampling method and purposive sampling was designed. Data were collected using a questionnaire with a Likert scale and then analyzed with Structural Equation Modeling (SEM) through the AMOS program version 21. The results of the analysis proved that Competence had a significant effect on Compensation; Compensation has a significant effect on Organizational Citizenship Behavior (OCB); Competence has a significant effect on Organizational Citizenship Behavior (OCB); Compensation has a significant effect on Job Performance; Organizational Citizenship Behavior (OCB) has a significant effect on Job Performance; Competence has a significant effect on Job Performance of life insurance in Batam City.